FACTORS AFFECTING EFFECTIVENESS OF CHANGE INITIATIVES: Evidence from Malaysian Firms - Ismail, Mohd Nazzari; Ahmad, Shreen (Gadjah Mada International Journal of Business, 2003)
This paper investigates various system models and change guidelines that deal with the dynamics of successful change. It seeks to find out whether Malaysian organizations which have achieved successful change outcomes would have also managed the change process in accordance to the general guidelines derived from the literature onÂ  effective management of change. Primary data for this study was obtained by conducting a mailed questionnaire survey among executives and managers of seventeen Malaysian organizations. The main method of analysis is byÂ  looking at the correlation between an organizationâs scores on the relevant items in the change process scales and the organizationâs perceived effectiveness of change, as measured by the organizationâs change effectiveness scores.The general finding confirms and reinforces the literature on effective change management.Â  It was found that organizations that were perceived by staff to have achieved successful change outcomes, were also perceived to have managed the change processes well in accordance to general principles derived from research on organizational change.